2009
DOI: 10.1002/hyp.7448
|View full text |Cite
|
Sign up to set email alerts
|

Modelling evapotranspiration using discrete wavelet transform and neural networks

Abstract: Abstract:This study combines wavelet transforms and feed-forward neural network methods for reference evapotranspiration estimation. The climatic data (air temperature, solar radiation, wind speed, relative humidity) from two stations in the United States was evaluated for estimating models. For wavelet and neural network (WNN) model, the input data was decomposed into wavelet sub-time series by wavelet transformation. Later, the new series (reconstructed series) are produced by adding the available wavelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…In this study, the significant wavelets (approximation and detail series) were summed together once the insignificant coefficients were excluded, similar to what was done by Partal [58] and Kisi and Cimen [32]. In this study, the summed sub-series provided better results than using the individual wavelet coefficients as inputs.…”
Section: Wn Modelsmentioning
confidence: 89%
“…In this study, the significant wavelets (approximation and detail series) were summed together once the insignificant coefficients were excluded, similar to what was done by Partal [58] and Kisi and Cimen [32]. In this study, the summed sub-series provided better results than using the individual wavelet coefficients as inputs.…”
Section: Wn Modelsmentioning
confidence: 89%
“…The WD-ARIMA model exhibited very good performance for forecasting the A ET , surplus, and deficit, whereas the classical ARIMA model exhibited poor performance or was unable to forecast the WBCs. Moreover, studies (Chou, 2011;Kisi, 2008;Partal, 2009;Santos and da Silva, 2014;Rahman and Hasan, 2014;Nury et al, 2016;Adamowski and Chan, 2011;Khalek and Ali, 2016) have indicated that the performance of wavelet-aided models is better than that of the classical ARIMA and ANN models for forecasting nonstationary hydrometeorological variables. Because traditional methods such as Wiener filtering, Kalman filtering, and Fourier transform are unsuitable for nonstationary hydrological time series data (Adamowski and Chan, 2011;Sang, 2013), wavelet denoising can be used to improve the performance of the classical ARIMA model for forecasting hydrological variables.…”
Section: Discussionmentioning
confidence: 99%
“…. D4 + D3 + A) of the time series data were calculated and the obtained results were compared (Partal and Küçük, 2006;Partal, 2009). …”
Section: Wavelet Transform (Wt) and Periodicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nourani et al [15] combined WA and ANN to predict the runoff in the Ligvanchai valley of Tabriz, Iran. Partal [38] conducted a reference evapotranspiration estimation using the wavelet transform and the feedforward neural network methods to evaluate climate data (temperature, solar radiation, wind speed, relative humidity) at two stations in the United States.…”
Section: Introductionmentioning
confidence: 99%